Patients and Parents’ Experience of Multi-Family Therapy for Anorexia Nervosa: A Pilot Study - Baumas, Victoria; Zebdi, Rafika; Julien-Sweerts, Sabrina; Carrot, Benjamin; Godart, Nathalie; Minier, Lisa; Rigal, Natalie (Frontiers in Psychology, 2021)
Abstract Background: Family therapy is considered as the gold standard in treatment of adolescents with Anorexia Nervosa (AN). Amongst the different types of family therapy, Multi-Family Therapy (MFT) is increasingly used for treating AN, and shows promising results. In this paper, our focus relied on the patients’ and their parents’ perceptions of the effectiveness and the underlying mechanisms of the MFT. Methods: The present pilot exploratory qualitative study included two focus groups conducted using a semi-structured approach: one with the adolescents (n=3), and another with one or two of their parents (n=4 mothers; n=2 fathers). The subjects discussed were the changes observed in both AN symptoms and family interactions following therapy, and the mechanisms underlying these changes. We crossed the perspectives of the adolescents and of the parents on these two points. Results: Qualitative analysis revealed that while both adolescents and parents had difficulties relating the changes they observed in the last year to MFT, they were able to say that the group cohesion had several positive effects and that their family dynamics had improved. In the light of analysis the adolescents perceived more improvements related eating disorders symptoms than their parents did, while parents were concerned about a negative effect of MFT on their children. Discussion: While both patients and parents perceived improvements in both AN symptoms and family interactions in the past year, it was not clear if they considered MFT to have led to these improvements. FG also explored the MFT mechanisms underlying changes. Both adolescents and their parents stressed the beneficial effects of identification to others members of the group and shared experience to overcome social isolation. Parents also mentioned the sympathy they felt for each other. The idea that they give a central place to families in the therapy was also described by the families.